Power of learning : fostering employee growth - Mellander, Klas (Irwin ChicagoUS, 1993)
Focuses on the need for individuals and organizations to learn effectively. Discusses the learning process and presents an overview of factors which promote or hinder learning. Provides strategies for solving learning problems. These include: mind mapping; collaborative learning; and the art of studying. Describes the characteristics of the learning organization and suggests guidelines for evaluating training.